Role of Amrita Guggulu in the management of Vata rakta A Clinical Trial - Srivastava, Alok Kumar (International Journal of Pharmaceutical & Biological Archive, 2015)
Role of Amrita Guggulu in the management of Vata rakta A Clinical Trial